IMPLEMENTASI HYBRID LEARNING DI MASA PANDEMI COVID-19 DALAM MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS V SD NEGERI 163080 TEBING TINGGI - Hayati Hayati (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This study aims to examine how the Hybrid learning model at SD Negeri 163080 Tebing Tinggi during the Covid-19 pandemic.  Various obstacles in implementing distance education require an appropriate learning model, including a Hybrid learning model. To improve students' understanding of the social science subject, done with class action research refers to the model of Kemmis and Mc. Taggart which consists of four components, namely: 1) planning, 2) implementation of the action, 3) observation, 4) reflection. A total number of 30 respondents were used as the samples determined based on qualitative descriptive analysis technique. The results showed there was improvement of student learning outcomes characterized by increased every cycle, namely pre-cycle (60%), the first cycle (76,67 %), cycle II (90 %) and complete learn the clasical equal to 90  %. This conclution is the application of problem solving method has real effect toward learning outcomes of students grade V at SD Negeri 163080 Tebing Tinggi in academic year on 2021/2022.